14th annual College of Veterinary Medicine and Biomedical Sciences research day scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2013)
Includes the Pfizer Research Award winner and abstracts only of the oral sessions and posters.
14th annual CVMBS research day scientific proceedings
CVMBS research day 2013
Held in the Fort Collins Hilton on January 23, 2013, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses